1985
DOI: 10.1017/s0043174500082345
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Morphological Characteristics of Red Rice (Oryza sativa) Biotypes

Abstract: Pot experiments were conducted in the field at Stuttgart, AR, during 1982 and 1983 to evaluate growth and morphological differences between strawhull and blackhull red rice (Oryza sativaL. ♯ ORYSA) biotypes collected from Arkansas, Louisiana, and Texas. All red rice biotypes were compared with rice (Oryza sativaL.) cultivars ‘Lebonnet’ and ‘Nortai’. Growth and morphological differences were greatest between cultivars and red rice biotypes, less between blackhull and strawhull types, and least among collections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 4 publications
4
54
1
1
Order By: Relevance
“…As noted by Diarra et al (1985a) red rice height advantage over rice was associated with red rice's superior competitiveness ( Figure 2). Red rice had no clear advantage in leaf area or early tillering over Oryzica 1 (Figure 1a, b, d and e).…”
Section: Growth Analysis Of Rice and Red Rice Biotypes In Competitionmentioning
confidence: 66%
“…As noted by Diarra et al (1985a) red rice height advantage over rice was associated with red rice's superior competitiveness ( Figure 2). Red rice had no clear advantage in leaf area or early tillering over Oryzica 1 (Figure 1a, b, d and e).…”
Section: Growth Analysis Of Rice and Red Rice Biotypes In Competitionmentioning
confidence: 66%
“…c ND and D mean non-deletion and deletion type ORF100, respectively. by direct seeding and by mechanical means (Oka 1988;Diarra et al 1994;Suh and Ha 1994;Catala-Forner 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The weedy rice complex mainly includes plants setting red pericarp seeds, known as red rice (Olofsdotter et al 2000), although some morphotypes have white pericarps (Herna´ndez et al 1979). Weedy rice plants are usually taller than commercial varieties, have more tillers and panicles per plant, but frequently produce less seed (Diarra et al 1985;Noldin et al 1999). Planting contaminated seed increases the infestation levels of weedy rice in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Several morphological studies of weedy rice have been reported in Colombia (Montealegre and Clavijo 1991), Venezuela (Ortiz et al 1999), Brazil (Agostinetto et al 2001), Mexico (Herna´ndez et al 1979) and the United States (Noldin et al 1999). Weedy rice has been traditionally classified as O. sativa L. subspecies indica or japonica, based on morphological characters (Diarra et al 1985;Langevin et al 1990;Kwon et al 1991) and molecular markers (RFLP and RAPDs) (Shu et al 1997;Federeci et al 2001). Furthermore, Vaughan et al (2001) demonstrated in a genetic study using microsatellites that weedy rice from Arkansas, Louisiana, Mississippi and Texas (USA) also included the Asian wild species O. nivara and O. rufipogon Griff.…”
Section: Introductionmentioning
confidence: 99%